HUBUNGAN ANTARA INDEKS MASSA TUBUH DAN KEKUATAN OTOT EKSTREMITAS BAWAH PADA ANAK USIA 7 - 12 TAHUN - Salsa Nabila, (2023)
Background: Early age in children around 7 to 12 years is the age where a child needs a situation and condition to develop growth and development. At that age they are in a condition that should still be active in physical activity. But technological advances such as gadgets or computers are able to hypnotize each child, causing children to become less active or move to explore the outside environment, resulting in a decrease lower. But other research states the opposite. This is caused by the factors that affect the two variables. Objective: This study aims to determine the relationship between the body's mass index and the strength of the lower limb muscle in children aged 7-12 years. Method: This study study is cross sectional with a correlative approach. The sample in this study totaled 130 people. The parameters used to measure the body's mass index (IMT) are IMT/U with WHO Anthroplus 2007 and parameters to measure muscle strength are standing long jump tests. Results: Based on the results of the normality test for the body's mass index and the strength of the lower limb muscles obtained the results of p <0.001 or p <0.05 and for the relationship between the body's mass index and the strength of the lower extremity muscles get the results of the value of P>0.150 or P>0.05. Conclusion: This study found that there was no significant relationship between the body's mass index and the strength of the lower limb muscle in children aged 7-12 years.